Coping and quality of life of patients following microsurgical treatment for breast cancer–related lymphedema. (December 2016) - Teo, Irene; Fingeret, Michelle Cororve; Liu, Jun; Chang, David W
Breast cancer–related lymphedema is associated with numerous adverse outcomes. This study investigated the extent clinical factors, lymphedema symptoms, lymphedema-related appearance, and coping strategies predicted quality of life. Female patients who underwent microsurgical treatment for lymphedema ( n  = 54) participated. Lymphedema symptoms were associated with physical and functional well-being, but not emotional and social well-being. Clinical factors and lymphedema-related appearance were not significantly associated with quality of life. Compared to adaptive coping strategies, maladaptive coping strategies (e.g. denial, venting, self-blame) were more strongly associated with quality of life. This suggests psychosocial interventions aimed at modifying maladaptive coping behaviors can potentially improve quality of life for this patient population.